Long-term oral administration of naringenin counteracts aging-related retinal degeneration via regulation of mitochondrial dynamics and autophagy - Chen, Guiping; Zeng, Ling; Yan, Feng; Liu, Jinlong; Qin, Mengqi; Wang, Feifei; Zhang, Xu (Frontiers in Pharmacology, 2022)
Aging-related retinal degeneration can manifest as decreased visual function due to damage to retinal structures and dysfunction in retinal homeostasis. Naringenin, a flavonoid, has beneficial effects in preventing cellular aging, preserving the functionality of photoreceptors, and slowing down visual function loss. However, the role and potential mechanism of naringenin in the aging mouse retina require further investigation. In this study, we evaluated the effects of naringenin on the aging eye using electroretinogram (ERG) and hematoxylin and eosin staining and explored its potential mechanism by western blotting. ERG showed that naringenin increased the amplitude of the a- and b-waves of scotopic 3.0, 10.0, and the a-wave amplitude of photopic 3.0 in the aging mouse retina. Furthermore, administration of naringenin prevented aging-induced retinal degeneration in the total retina, ganglion cell, inner plexiform layer, inner nuclear layer, and outer nuclear layer. The expression of mitochondrial fusion protein two was increased, OPA1 protein expression and the ratio of L-OPA1/S-OPA1 were unchanged, and dynamin-related protein one was decreased in the 12-month-old mice treated with naringenin compared with the 12-month-old mice treated with vehicle. Furthermore, the downregulation of age-related alterations in autophagy was significantly rescued in the aging mice by treatment with naringenin. Taken together, these results suggest that the oral administration of naringenin improves visual function, retinal structure, mitochondrial dynamics, and autophagy in the aging mouse retinas. Naringenin may be a potential dietary supplement for the prevention or treatment of aging-related retinal degeneration.